2012
DOI: 10.1111/j.1440-1797.2012.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian consumer perspectives on dialysis: First national census

Abstract: The delivery of pre-dialysis education is variable, and does not support all options of dialysis for all individuals. State variances indicate that local policy and health professional teams significantly influence the operation of dialysis programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…More than one third (39%) did not remember having received any information on alternative treatment options than their current one. A similar study in Australia also found that 49% of respondents indicated that they had had no choice in the type of dialysis [49] . Moreover, patients were twice as likely to receive information about HD than about CAPD or APD.…”
Section: Effect Of Patient Preference and Contraindications On Modalimentioning
confidence: 84%
“…More than one third (39%) did not remember having received any information on alternative treatment options than their current one. A similar study in Australia also found that 49% of respondents indicated that they had had no choice in the type of dialysis [49] . Moreover, patients were twice as likely to receive information about HD than about CAPD or APD.…”
Section: Effect Of Patient Preference and Contraindications On Modalimentioning
confidence: 84%
“…The average timing of education delivery was during stage 4–5, with a reported 82% of patients receiving education prior to treatment. PINOT similarly found that the average eGFR of patients receiving education was 13.3 mL/min and that 84% of patients received information prior to treatment, 72% of incident patients were documented to have received PD, and 52% HHD education …”
Section: Discussionmentioning
confidence: 97%
“…Despite all renal units placing a high value on the presence of significant others to support the patient with ESKD, many patients attended education alone. The PINOT study found that only 20% of patients started on home dialysis, but 80% of these had a care‐giver present at education, compared with only 56% of those who started at a centre . Care‐givers and future patients in Italy reported they were concerned about the potential burden of home dialysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also strongly suggested that the education and decision‐making processes they experienced were not always comprehensive (Ludlow et al . ).…”
Section: Introductionmentioning
confidence: 97%